Metaanalysis of the TQM impact on business performance amongst regions and countries. (2015) - Ahmad, M.F.; Zakuan, N.; Ahmad, J.; Takala, J.
Metaanalysis has been conducted based on 20 previous works from 4, 040 firms at 16 countries from Asia, Europe and USA. Throughout this paper, the metaanalysis is applied to review the impact of TQM on business performance amongst the regions and countries. The result of metaanalysis shows that the average of regression coefficient (rc) is 0.47; Asia (rc = 0.54), USA (rc = 0.43) and Europe (rc = 0.38). Asia developed countries have the greatest impact of TQM towards business performance (rc = 0.56). ANOVA and ttest have been conducted to test the difference amongst type of country (developed and developing countries) and regions at p = 0.05. However, the result shows that there is no significant difference. In addition, rc2 of each country have been calculated based on rc value and the average result of rc2 is 0.24; Asia (rc2 = 0.33), USA (rc2 = 0.22) and Europe (rc2 = 0.15). Meanwhile, rc2 in developing countries (rc2 = 0.28) are higher than developed countries (rc2 = 0.21).